2005
DOI: 10.1002/elps.200410317
|View full text |Cite
|
Sign up to set email alerts
|

Chiral ion‐exchange capillary electrochromatography of arylglycine amides with dextran sulfate as a pseudostationary phase

Abstract: A low-cost tunable chiral ion-exchange capillary electrochromatographic method has been developed for the separation of arylglycine amide racemic mixtures with dextran sulfate (DS) as an anionic and chiral pseudostationary phase and Tris-tartrate as a buffer system. The concentrations of DS and Tris had opposite influences on retention and resolution and could serve as ideal factors to finely tune the running speed and chiral resolution. Tartrate and pH largely impact the separation but pH should be confined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Although ligands are important in performing CLE-CE due to the exchange mechanism [16], the frequently used central ion Cu(II) [17] is also replaceable, namely by Mn(II), Zn(II), Ni(II), and even B(III) or borate [18][19][20][21][22][23][24][25][26]. Kodama et al [23] have demonstrated that borate was effective in the separation of D,L-pantothenic acid because it is capable of forming complex with the cis-1,2-or 1,3-hydroxy.…”
Section: Introductionmentioning
confidence: 99%
“…Although ligands are important in performing CLE-CE due to the exchange mechanism [16], the frequently used central ion Cu(II) [17] is also replaceable, namely by Mn(II), Zn(II), Ni(II), and even B(III) or borate [18][19][20][21][22][23][24][25][26]. Kodama et al [23] have demonstrated that borate was effective in the separation of D,L-pantothenic acid because it is capable of forming complex with the cis-1,2-or 1,3-hydroxy.…”
Section: Introductionmentioning
confidence: 99%
“…The separation of ten arylglycine amide enantiomers was reported using dextran sulfate as the chiral PSP [40]. Substituent effects indicated that ionic interactions, hydrogen bonding, and steric factors were responsible for the chiral selectivity.…”
Section: New Polymersmentioning
confidence: 98%
“…Chen et al [69] applied dextran sulfate as an anionic pseudostationary phase using Tris/tartrate as a buffer system for the chiral separation of arylglycine amides. The authors call this technique ion-exchange CEC; however, since dextran sulfate forms a pseudostationary phase, it would be rather classified as EKC.…”
Section: Ekcmentioning
confidence: 99%